2020
DOI: 10.1088/1361-6641/abc456
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of off-state and hard-switching stress in gallium nitride-based power transistors

Abstract: The aim of this paper is to improve the understanding of gallium nitride (GaN) high electron mobility transistors (HEMTs) submitted to hard switching operation, with focus on the hot-electron phenomena. This is becoming a hot-topic both for the scientific community and for the industry. The analysis is carried out through a cross-comparison of three different experimental techniques: conventional Pulsed-IV characterization, a novel pulsed-drain current transient (P-DCT) method, and a custom-developed hard swit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…On the practical side, traps characterization based on device current variations can be performed by means of drain current DLTS (ID-DLTS) [478], [479], constant drain-current DLTS/DLOS (CID-DLTS/DLOS) [373], [480] or multiple DCTs measurements carried out at different temperatures [390], [481]. Pulsed drain-current methodologies have also been proposed, to characterize the de-trapping processes in absence of applied bias [482].…”
Section: Current Transientsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the practical side, traps characterization based on device current variations can be performed by means of drain current DLTS (ID-DLTS) [478], [479], constant drain-current DLTS/DLOS (CID-DLTS/DLOS) [373], [480] or multiple DCTs measurements carried out at different temperatures [390], [481]. Pulsed drain-current methodologies have also been proposed, to characterize the de-trapping processes in absence of applied bias [482].…”
Section: Current Transientsmentioning
confidence: 99%
“…Based on the comments and issues reported in this section, the authors would like to suggest that, to have an accurate estimation of the trap activation energy, VDS voltages applied during the sensing condition should be as low as possible, in order to reduce self-heating and electric field related enhanced emission. The use of pulsed-drain current transient (P-DCT) methodologies can also be effective to this aim, since the device is kept at zero bias during recovery, and short voltage pulses are used to sense the onresistance during the de-trapping phase [482].…”
Section: Bias Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these considerations, we demonstrate the applicability of the developed mathematical framework to the trap-state mapping in in normally-off p-GaN HEMTs after semi-on stress. During this stress condition, the device must sustain a simultaneously high drain-to-gate electric field and carrier density 26 . The carriers accelerated by the high field are described as “hot”, and their excess kinetic energy may favor trapping effects that are not reachable under normal (off-state) conditions.…”
Section: Experimental Trap-state Mapping On Gan-based Transistorsmentioning
confidence: 99%
“…Such trapping phenomena need to be analyzed and modeled: state-of-the-art approaches [15]- [17] reproduce trapping/detrapping phenomena as pure exponentials, an approximation that is only valid for ideal point defects, with a single energy level; following this idea, Kellogg et al [16] proposed a method to model defects in GaN HEMTs making use of a three-pole RC circuit. However, pure exponentials are generally not representative of real trapping kinetics [18]. In the presence of multiple traps, Li et al [17] suggested an iterative algorithm to extract multiple RC units with minimized error.…”
mentioning
confidence: 99%